2011
DOI: 10.1002/hed.21492
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and positron emission tomography‐CT evaluation for recurrent papillary thyroid carcinoma: Meta‐analysis and literature review

Abstract: PET and PET/CT are useful modalities in surveillance of papillary thyroid carcinoma. To our knowledge, this is the first study to examine papillary thyroid carcinoma independently of other subtypes of well-differentiated thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…In children, the neck and chest are the most likely sites of persistent disease, and contrast-enhanced imaging of these areas with CT or MRI is favored when US cannot identify disease. 18 FDG-PET/CT has become a commonly used tool in the evaluation of adults with persistent non-iodine-avid thyroid cancer (3,(321)(322)(323)(324)(325)(326) and appears to offer prognostic information that might change clinical management (327)(328)(329)(330). However, there are extremely limited data regarding the use of 18 FDG-PET/CT in children except for a case report (331), isolated pediatric subjects embedded within adult studies, and unpublished data that suggest low sensitivity of 18 FDG-PET/CT to identify residual disease in children that otherwise cannot be identified via cervical US and crosssectional imaging of the neck and chest (personal communication, SGW).…”
Section: Recommendation Rating: C and Recommendation 25(b)mentioning
confidence: 99%
“…In children, the neck and chest are the most likely sites of persistent disease, and contrast-enhanced imaging of these areas with CT or MRI is favored when US cannot identify disease. 18 FDG-PET/CT has become a commonly used tool in the evaluation of adults with persistent non-iodine-avid thyroid cancer (3,(321)(322)(323)(324)(325)(326) and appears to offer prognostic information that might change clinical management (327)(328)(329)(330). However, there are extremely limited data regarding the use of 18 FDG-PET/CT in children except for a case report (331), isolated pediatric subjects embedded within adult studies, and unpublished data that suggest low sensitivity of 18 FDG-PET/CT to identify residual disease in children that otherwise cannot be identified via cervical US and crosssectional imaging of the neck and chest (personal communication, SGW).…”
Section: Recommendation Rating: C and Recommendation 25(b)mentioning
confidence: 99%
“…However, both imaging procedures have limitation: US cannot image lesions outside the neck and may not detect lymph node micrometastases, and 131 I-WBS has poor accuracy when progressive dedifferentiation of tumour cells has occurred [2]. In the latter cases 18 F-FDG PET/CT has been shown to improve detection and localization of tumour foci [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 97%
“…The early detection of iodinenegative DTC lesions is important, because it triggers an adjustment in the treatment strategy: surgical resection, external-beam radiation therapy (EBRT), or multikinase inhibitor therapy will be selected rather than 131 I treatment. 18 F-FDG PET/CT is useful for the detection of recurrent DTC lesions, especially in patients with iodine-negative tumors and elevated serum thyroglobulin levels (6)(7)(8)(9)(10). Furthermore, recent studies showed that 18 F-FDG PET can detect DTC lesions more accurately under thyroid-stimulating hormone (TSH) stimulation than under TSH suppression (11)(12)(13).…”
mentioning
confidence: 99%